Hyper-Interleukin-6 Protects Against Renal Ischemic-Reperfusion Injury—A Mouse Model - Zuaiter, Mohammad; Axelrod, Jonathan H.; Pizov, Galina; Gofrit, Ofer N. (Frontiers in Surgery, 2021)
Background: Most of the ischemia-reperfusion injury (IR-I) occurs during reperfusion and is mediated by the immune system. In this study we determined whether immunomodulation with hyper-Interleukin-6 (a recombinant designer cytokine composed of interleukin-6 linked to its soluble receptor) is protective against IR-I in mice kidneys. Methods: Hyper-Interleukin-6 (HIL-6) was administered by in vivo plasmid DNA transfection to 10 male mice. Twenty-four hours later, unilateral nephrectomy was done. IR-I immediately followed by closure of the remaining kidney vascular pedicle for 40 min. Seven mice transfected with non-coding control plasmid served as the control group. The functional and morphological effects of IR-I and its effect on mice longevity were explored. This was done by serial blood tests and by histopathology done upon sacrifice of the animals at post-operative day 7. Findings: Mice pretreated with HIL-6 had a mean creatinine level at post-operative day 1 of 35.45 ± 4.03 μmol/l and mean Urea level was 14.18 ± 2.69 mmol/l, whereas mean creatinine was 89.33 ± 69.27 μmol/l (P = 0.025), and mean urea was 38.17 ± 20.77 mmol/l (P = 0.0024) in the control group. Histological changes in the control group included inflammatory infiltration, tubular damage, and architectural distortion. These were not seen in the treatment group. Seven days post-operatively the survival rate of treated mice was 100% compared to 50% in the control group (P = 0.015). Interpretation: In this single kidney mouse model, pretreatment with HIL-6 administration effectively protected against IR-I both morphologically and functionally. Further studies are needed to better understand the mechanism and feasibility of using this immunomodulator.